Potential winter-season bias of annual temperature variations in monsoonal Tibetan Plateau since the last deglaciation. (15th September 2022) - Sun, Zhe; Hou, Xiaohuan; Ji, Kejia; Yuan, Kan; Li, Can-ge; Wang, Mingda; Hou, Juzhi
Abstract: Knowledge of paleotemperature variation in the Tibetan Plateau (TP) can provide potential insights to evaluate the future climate change under ongoing global warming and to improve our understanding of the controversial Holocene temperature changes between stacked proxy and model simulation. Here, we present a 115-yr-resolution record of bGDGTs (branched glycerol dialkyl glycerol tetraethers) based mean annual air temperature (MAAT) from Ngamring Co in the southern TP, spanning the past 18 ka. Our record reveals the MAAT generally responds to annual insolation and greenhouse gases changes, showing slight cooling during the deglaciation and remaining at low temperature until 6 ka BP, and then warming up to present. Combination with other records reveals the regional annual temperature shows a warming trend in the Holocene, which is in agreement with the model simulation rather than the stacked proxies. Importantly, the distinct cold interval during 10–6 ka BP is not present either in the simulation or in most of records for the adjacent region. We suggest such cold interval was a response to the positive North Atlantic Oscillation (NAO) conditions during the early Holocene, which led to a decrease in winter temperature and increased snowfall in the southern TP. Considering the consistent pattern of local annual and winter insolation over past 18 ka, and the high correlation between annual and winter temperature over the past 40 yr, we cautiously indicate that winter season may be crucial for the annual temperature in the TP. Additional quantitative records with clear seasonal signals, especially in winter, are needed to confirm our hypothesis. Highlights: A bGDGTs-based MAAT temperature shows a fluctuation of ∼9 °C in the southern Tibetan Plateau during past 18 ka. A slightly cooling trend in the last deglaciation and a warming trend in the Holocene were observed in the new record. The MAAT is mainly reconciled by local annual insolation and CO2 changes. Winter season may be crucial for the annual temperature.